Phosphorylation of Human Papillomavirus Type 16 L2 Contributes to Efficient Virus Infectious Entry - Broniarczyk, Justyna (J Virol, 2019)
The human papillomavirus (HPV) capsid comprises two viral proteins, L1 and L2, with the L2 component being essential to ensure efficient endocytic transport of incoming viral genomes. Several studies have previously reported that L1 and L2 are posttranslationally modified, but it is uncertain whether these modifications affect HPV infectious entry. Using a proteomic screen, we identified a highly conserved phospho-acceptor site on the HPV-16 and bovine papillomavirus 1 (BPV-1) L2 proteins. The phospho-modification of L2 and its presence in HPV pseudovirions (PsVs) were confirmed using anti-phospho-L2-specific antibodies. Mutation of the phospho-acceptor sites of both HPV-16 and BPV-1 L2 resulted in the production of infectious virus particles, with no differences in efficiencies of packaging the reporter DNA. However, these mutated PsVs showed marked defects in infectious entry. Further analysis revealed a defect in uncoating, characterized by a delay in the exposure of a conformational epitope on L1 that indicates capsid uncoating. This uncoating defect was accompanied by a delay in the proteolysis of both L1 and L2 in mutated HPV-16 PsVs. Taken together, these studies indicate that phosphorylation of L2 during virus assembly plays an important role in optimal uncoating of virions during infection, suggesting that phosphorylation of the viral capsid proteins contributes to infectious entry. IMPORTANCE The papillomavirus L2 capsid protein plays an essential role in infectious entry, where it directs the successful trafficking of incoming viral genomes to the nucleus. However, nothing is known about how potential posttranslational modifications may affect different aspects of capsid assembly or infectious entry. In this study, we report the first phospho-specific modification of the BPV-1 and HPV-16 L2 capsid proteins. The phospho-acceptor site is very highly conserved across multiple papillomavirus types, indicating a highly conserved function within the L2 protein and the viral capsid. We show that this modification plays an essential role in infectious entry, where it modulates susceptibility of the incoming virus to capsid disassembly. These studies therefore define a completely new means of regulating the papillomavirus L2 proteins, a regulation that optimizes endocytic processing and subsequent completion of the infectious entry pathway.